A two-element planar multiple input multiple output array for ultra-wideband applications - Abdul Kayum Mohammad Zakir Hossain; Muhammad Ibn Ibrahimy; Tole Sutikno; Mohd Hatta Jopri; Jamil Abedalrahim Jamil Alsayaydeh; Mustafa Manap (International Journal of Electrical and Computer Engineering (IJECE), 2022)
In this article, a planar monopole two-element multiple input multiple output (MIMO) array has been designed and characterized with the intention of ultra-wideband (UWB) applications. The array has a voltage standing wave ratio (VSWR) working bandwidth (BW) of 13.258 GHz between 3.394-16.652 GHz, with a fractional BW (FBW) of 132.28% with respect to a center frequency of 10.023 GHz. The two elements of the MIMO array are 900 polarizations mismatched for better isolation. Consequently, less than 20 dB of isolation has been achieved throughout the entire BW. Also observed was a good combined realized peak gain of up to 5.85 dBi and total efficiency of greater than 85%. For MIMO performance key parameters, the array exhibits the envelope correlation coefficient (ECC) <0.0033, diversity gain (DG) >9.983, total active reflection coefficient (TARC) <0.445, mean effective gain difference (MEG12) ≈0 dB, and the channel capacity loss (CCL) <0.4 bps/Hz. This design would encourage designers to create high-performance MIMO antennas for UWB frequency-related applications.